(untitled) (Archives of Criminology, 2023)
Writing about the progress in the fight against forced labor, the UN Special Rapporteur on Trafficking in Human Beings Maria Grazia Giammarinaro in 2020 said that were still at an “early stage”. It may be surprising if we take into account that International Convention on this issue was adopted over 80 years ago. Forced labor has two basic components: the labor exploitation and migration – both of them socially distressing. But from the point of view of the public life, the most painful is the juxtaposition of two figures: 40,000,000, i.e. estimation of the global number of victims of various forms of enslavement, and 100,000 – this is more or less the number of victims identified yearly by law enforcement agencies around the world. Even so, many countries still do not have any policies to combat forced labor but the interest of politicians is weakened by the needs of economic development. Finally, this non optimistic picture is combined with relatively low level of awareness of many social groups and the prevailing false belief that the real problem is the sexual exploitation of women and children. These were the reasons why we considered the publication of a Special Issue of the Archives of Criminology as necessary. The articles in this volume offer a number of interesting reflections and bring many innovative ideas.